Functional Limitations in Patients with Diabetic Neuropathy: Prevalence, Optimal Cut-off Points, and Impact on Physical and Mental Health - Khamnon, Narongsak; Sitthiracha, Pairaya; Suwannarat, Phannarin; Jiamjunyasiri, Areeya; Kaewjoho, Chonticha (Malaysian Journal of Medical Sciences, 2025)
Background: This study aimed to examine the prevalence of functional limitations, compare physical ability and mental health between diabetic participants with diabetic peripheral neuropathy (DPN) who had and did not have functional limitations, and determine the correlations, cut-off points, area under the curve (AUC), sensitivity, and specificity of various physical performance tests for identifying individuals with these limitations.Methods: The participants’ baseline characteristics and neuropathy severity were assessed. Functional limitations and mental health were evaluated using the 9-Question Depression Screening tool (9Q) questionnaire, while physical abilities were measured by handgrip strength (HG), the Five Times Sit To Stand Test (FTSTS), Timed Up and Go (TUG), the 10-m walk test (10MWT), and the 2-min step test (2MST).Results: Among the participants with DPN, 58% had at least one functional limitation, most commonly walking up 10 steps (86.8%), performing leisure activities (63.2%), and stooping or rising from a chair (27.9%). Those with limitations had significantly lower mental health, muscle strength, balance, and endurance (P < 0.05). Functional limitations correlated moderately with HG, FTSTS, TUG, 2MST, and 10MWT (P < 0.001) and mildly with 9Q score. 10MWT showed the strongest predictive ability (AUC = 0.927), while other tests demonstrated moderate to high accuracy (AUC = 0.692–0.899).Conclusion: Over half of the individuals with DPN experienced at least one functional limitation, most commonly affecting mobility and daily activities. Those with limitations exhibited poorer dynamic balance, muscle strength, and endurance. Among the physical performance tests, 10MWT demonstrated the strongest predictive ability (cut-off = 0.75 m/s, AUC = 0.927), underscoring its reliability and efficiency in identifying functional limitations in this population.